ISSUES IN SANAD AND THEIR IMPLICATIONS FOR EARLY CHILDHOOD ISLAMIC EDUCATION - Pujiniarti, Yayu Bondan (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Purpose: This study examines the issues of the sanad of the tarbawi hadith and its implications for early childhood education at Raudhatul Athfal. Method: Using a qualitative approach based on literature studies, this study examines the quality of the sanad of the hadith, which is often used as the basis for the curriculum and learning practices in Islamic educational institutions. Result: The results show that not all tarbawi hadith used are authentic; some are hasan, daif, or even maudhu'. Conclusion: This finding emphasizes the importance of RA teachers' caution in using hadith as the basis for principles and parameters for shaping children's behavior. Sahih hadith on prayer, compassion, the prohibition of violence, and the Prophet's relationship with children are proven to align with the principles of modern, compassion-based education. Meanwhile, popular daif hadith such as